Evaluasi Perbaikan Tanah Menggunakan Geotekstil Untuk Meningkatkan Stabilitas Tanah Lapisan Subgrade Pekerjaan Jalan - Z Lubis, Mhd Khuzeir; lubis, Kamaluddin (JCEBT (JOURNAL OF CIVIL ENGINEERING, BUILDING AND TRANSPORTATION), 2019)
At the stage of a construction work one of the main problems in soft soil is the large land decline. The large decrease is due to the decrease in soil. The condition of poor base soil in the form of clay soil needs to be done to improve the basic soil to be able to support the construction load. One method used as land improvement is by geotextiles. The type of geotextile used in the construction of the Medan-Kualanamu-Tebing Tinggi toll road project, Parbarakan-Lubuk Pakam Sta.42 + 750-Sta.47 + 600 is a geotextile PP woven polypropylene. The geotextile type uses non woven geotextile while the study is geotextile polypropylene woven, Non woven tensile strength 20 kN / m required 1 layer of geotextile while tensile strength Polypropylene woven 30 kN / m required 2 layers of geotextile. From these calculations can be concluded that the use of geotextiles can be used as one of the repair and retrofitting.